The Impact of Intangible Assets on Firms Earnings Profitability: Evidence from the Athens Stock Exchange (ASE) - Emmanouil, Gkinoglou; Dimitrios, Ginoglou (Archives of Business Research, 2017)
The present paper examines the effects of intangible assets in the return on equity and return on assets during the period from the begging of adopting International Accounting Standards (IAS) on financial statements and before the start of the Greek economic crisis. At this paper, is trying an effort for the contribution of the Intangible Assets as a very important part of the assets of the company but still ”unmeasurable”, but definitely main account for future gains. In this research study, using a dataset of Greek listed firms in the Athens Stock Exchange (ASE) is made an attempt to investigate the hypothesis that the firms that have large intangible assets have better return on equity and better return on assets for the Greek listed companies, during the period 2004 -2009, the most significant business period for the entire greek economy and especially for the listed greek companies in the Athens Stock Exchange (ASE), just before the start of the catastrophic Greek crisis. In conclusion, this study indicates that there are accounting and auditing problems of defined, measured and disclosed intangible assets to users of financial statements. Despite these problems the importance of intangible assets will increase, as the market grows and there is a constant need to supply reliable accounting information.